McGillycuddy could! - Edwards, Pamela Duncan (Katherine Tegen Books, 2005)
Although McGillicuddy the kangaroo cannot produce wool or milk or lay eggs, the other animals learn that kangaroos can bring special skills to the farm. Library of Congress Summary. Although McGillicuddy the kangaroo cannot produce wool or milk or lay eggs, the other animals learn that kangaroos can bring special skills to the farm. Annotation. McGillycuddy is new to the farm. What use is McGillycuddy, wonder the cow, sheep, hen, and rooster. She can't make milk. She can't lay eggs. She can't even "Cock-a-doodle- doo!" So what do McGillycuddys do? Young readers will delight in this boisterous read-aloud and enjoy discovering all the special things a McGillycuddy can do!